PENGARUH SOCIAL MEDIA MARKETING MELALUI OFFICIAL ACCOUNT LINE ALFAMART TERHADAP MINAT BELI KONSUMEN - Nurfitriani "; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The development of internet marketing also encourage users of social media in marketing communications, or can be called as social media marketing. One of social media marketing is now popular among businesses these days is Instant Messanging (IM) LINE. The features from official account LINE is a feature that allows users who’re friends with the official LINE account to get a variety of information, and also promotion from the owner of the official account. This opportunity used by PT . Sumber Alfaria Trijaya, Tbk (Alfamart) to also make an official account LINE Alfamart. The messages posted by that account aims to Alfamart as a modern retail and to promote its products in order to arise consumers to buy the products they've offered. The purpose of this research is to determine how much the influence of social media marketing from official account LINE Alfamart towards the interest to buy of consumer.The theory used in this study is S-O-R theory by Hovland.The method used in this study is a quantitative method of explanation. Researchers collected data using questionnaires and documentation. This research is not confined to just one area only because of the totaled 271 respondents which is selected by using simple random sampling methode whose followed official account LINE Alfamart were live in different regions. In order to know how much the influence from variable X and Y, researchers used a simple linear regression analysis. As for processing test data questionnaire, carried out using the program of Statistics Product and Service Solution (SPSS) Windows version 20.The result of simple linear regression to study the influence of social media marketing from official account LINE Alfamart towards the interest to buy of consumer, the regression values obtained in this study is Y = 21,400 + 0,471 X with significant level of 0,000. It’s mean smaller than α = 0,05. That is to say, there is influence of social media marketing from official account LINE Alfamart towards the interest to buy of consumer of 17,5% in the category very weak. Although is not dominant, but the respondents are paid attention to the content of the message and there is interest to buy at Alfamart. Accordingly H0 is rejected and Ha is accepted.Key Word : Social Media Marketing, Interest to Buy, LINE, Alfamart